STRUKTUR DAN POLA KEPEMIMPINAN KYAI DALAM PESANTREN DI JAWA - Fadhilah, Amir (Hunafa: Jurnal Studia Islamika, 2011)
Abstract: The world of pesantren and the IslamicÂ clericsâÂ  charisma Â is one of theÂ interesting phenomenaÂ toÂ be studied. The styleÂ ofÂ clericsâ lifeÂ andÂ religious studentsÂ  is so great that it makes Islamic boardingÂ  school posess a multi-dimensionalÂ  function: The KyaisÂ notÂ only are not only required asÂ priestsÂ in religiousÂ  ceremoniesÂ  and ritualsÂ , butÂ also oftenÂ  requiredÂ her presence Â toÂ  resolveÂ  the caseÂ or the difficultiesÂ  that Â befallÂ  the community.Â InÂ this context,Â  the role of the Islamic clericsÂ  is increasingly rootedÂ  inÂ the communityÂ whenÂ their presencesÂ  are believedÂ  to bring fortune.Â The existence ofÂ  structuresÂ  andÂ patterns ofÂ  authorityÂ  (leadership) clericsÂ  in the IslamicÂ  worldÂ  remainÂ  sustainable,Â  becauseÂ  the Islamic clericsÂ  haveÂ  internal socialÂ netsÂ  (among Â theÂ religious schools)Â  and Â  externalÂ  social netwoeks (withÂ  the world Â Â outsideÂ  pesantren),Â  includesÂ  genealogicalÂ  network, Â ideological network, Â intellectualÂ  network, theologicalÂ  network, and spiritualÂ network.Kata Kunci: pola kepemimpinan kyai, pesantren, kharismatik dan jaringan